Control over government: institutional isomorphism and governance dynamics in German public administration - Lodge, Martin; Wegrich, Kai (2005)
The era of public management change is said to challenge traditional "command and control" modes of governance, encouraging a move toward either more informal forms of (c0-_ governance or market-type incentives and competition. Regardless of whether these claims are made by reform advocates or by more sceptical observers within the wider governance debate, less attention has been paid by either side on the mechanisms that are supposed to facilitate the spread of new forms of control. This article seeks to advance this state of affairs in two ways. First, it utilizes the notion of institutional isomorphism to explore the nature of change of modes of control. In particular, it assesses the mechanisms for change, whether control mechanisms in the federal context of Germany in two policy domains, prison and local government supervision (in the field of building administration). Finally, this article suggests that cultural theory offers considerable insights for the study of institutional isomorphism by emphasizing conflicting worldviews and the diversity of related policy ideas as driving forces of change in modes of governance. - Reproduced.
Keywords: Public administration - German; Public administration